We know the derivative of ex, which is ex.
(ex)' = ex
We can find the derivative of e√cscx using chain rule.
Find ᵈʸ⁄dₓ, if
y = e√cscx
Let u = cscx.
y = e√u
Let v = √u.
y = ev
y = ev ----> y is a function of v
v = √u ----> v is is a function of u
u = cscx ----> u is is a function of x
By chain rule, the derivative of y with respect to x :
Substitute y = ev, v = √u and u = cscx.
Substitute v = √u.
Substitute u = cscx.
Kindly mail your feedback to firstname.lastname@example.org
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM